La mobilité quotidienne conduit-elle les Parisiens à respirer un air plus ou moins pollué ? - Laurent Proulhac; Alexis Poulhès (VertigO)
This article proposes a dynamic assessment of the exposure to air pollution of the urban population of the Paris region (France). The original methodology takes into account the variability in space and time of pollutants and inhabitants. It is based on the cross-referencing of NO2 concentration data (Airparif) and daily mobility data of a representative sample of inhabitants (Île-de-France Mobilités–OMNIL–DRIEA). The results underline the determining role of daily mobility in the level of individual exposure to pollution. Compared to the reference exposure at home, daily mobility leads the inhabitants of Paris region to deteriorate their NO2 exposure level by 1.1 µg/m3 (+4%) on average, to 32.1 µg/m3. The differentiated mobility of inhabitants according to the use of individual motorized modes and the time spent in Paris leads to an unequal deterioration of the quality of the air they breathe. For working people, students and residents of the outer suburbs, their daily mobility tends to significantly increase their exposure to NO2, unlike that of inactive people and residents of Paris.